1991
DOI: 10.1524/zkri.1991.194.14.305
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of rutile as a function of temperature up to 1600° C

Abstract: The crystal structure of rutile (Ti0 2 ) has been studied at high temperatures up to about 1600°C based on sets of single crystal X-ray diffraction intensities collected on a four-circle diffractometer. The thermal expansion coefficients for the a-and c-axes in the measured temperature range were a" = 8.9(1) χ 10" 6 °C _I and ot c = 11.1(1) χ 10~6 °C _1 , respectively. The thermal response of the octahedra about Ti is such that the thermal coefficient for the four short equatorial Ti -Ο bonds was 8.4(3) χ 10 "… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
56
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 11 publications
7
56
0
Order By: Relevance
“…Some degree of texture is evident upon comparing the XRD pattern obtained from the coating with the powder diffraction pattern for the rutile phase. 8 We invariably Fig. 2.…”
Section: Analysis and Resultsmentioning
confidence: 91%
“…Some degree of texture is evident upon comparing the XRD pattern obtained from the coating with the powder diffraction pattern for the rutile phase. 8 We invariably Fig. 2.…”
Section: Analysis and Resultsmentioning
confidence: 91%
“…Moreover, the combination and formation of several phases in this range have been predicted by the theory of reconstructive phase transitions [21,22] and also in the phase diagram schematic mentioned earlier. In addition, it has been observed that the stability of the a phase is maintained between room temperature up to 923 K (650°C), because with an increase in temperature, the aforementioned phase would gradually disappear and lead to the formation of titanium oxide (TiO 2 ) with the mineralogical name of rutile and the unit cell parameters a = 4.6001 Å and c = 2.9654 Å , [23] which is clearly observable at the temperature of 1003 K (730°C) and is completed at 1183 K (910°C). This result is, in fact, in good agreement with the theoretical predictions of References 9, 12, and 21.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature dependence of the unit cell volume and coefficient of volume thermal expansion (CVTE) curves at zero pressure are shown in figures 1a and 1b. It can be seen from figure 1b, that at all temperatures, the results of Debye-Grüneisen calculations are lower and are in better agreement with the experimental data[16,17]. Infigure 1(c), the values of the bulk modulus obtained from two models are compared.…”
mentioning
confidence: 57%
“…Phase transitions from and to rutile have been investigated by many researchers [7][8][9][10][11][12][13][14][15]. The coefficient of thermal expansion (CTE) have been reported by Krishna Rao et al [16], Sugiyama and Takéuchi [17] and Henderson et al [18]. Ligny et al [19] and Yong et al [20] reported the heat capacities and Fritz [21] measured the pressure and temperature dependences of the elastic properties of rutile.…”
Section: Introductionmentioning
confidence: 99%